2017
DOI: 10.1080/10934529.2017.1394701
|View full text |Cite
|
Sign up to set email alerts
|

State of the art of the environmental behaviour and removal techniques of the endocrine disruptor 3,4-dichloroaniline

Abstract: In recent years, the presence of Endocrine Disrupting Chemicals (EDCs) in wastewater discharges from agricultural and industrial sources, fresh- and estuarine-waters, as well as soils, has been reported in the literature. Studies of adverse changes in wildlife, linked to environmental exposure to these substances, and the suggestion that humans could also be at similar risk of adverse health effects, have raised concern for urgent action to understand and reduce such risks. 3,4-Dichloroaniline (3,4-DCA) has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…Chloroanilines are xenobiotic, carcinogenic and toxic substances known to hinder both nitrogen and carbon removal in wastewater treatment bioreactors (Falk and Wuertz, 2010). These compounds are intermediate breakdown products from the use of pesticides and herbicides in agriculture (Verhagen et al, 2015), which can be found in polymer, dye, pharmaceutical and rubber industrial wastewater treatment plants (Jen et al, 2001;Boon et al, 2003), but also in soil and natural aqueous environments (Tasca and Fletcher, 2017). A microcosm design allowed us to test a wide range of disturbances with good replication, while minimizing confounding factors across replicates (Drake and Kramer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chloroanilines are xenobiotic, carcinogenic and toxic substances known to hinder both nitrogen and carbon removal in wastewater treatment bioreactors (Falk and Wuertz, 2010). These compounds are intermediate breakdown products from the use of pesticides and herbicides in agriculture (Verhagen et al, 2015), which can be found in polymer, dye, pharmaceutical and rubber industrial wastewater treatment plants (Jen et al, 2001;Boon et al, 2003), but also in soil and natural aqueous environments (Tasca and Fletcher, 2017). A microcosm design allowed us to test a wide range of disturbances with good replication, while minimizing confounding factors across replicates (Drake and Kramer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we hypothesized that press disturbance by a xenobiotic would alter function, structure and assembly of sludge bioreactor bacterial communities. Chloroanilines are toxic substances that can easily diffuse within the natural environment and are difficult to remediate, posing an environmental problem for natural waters and soils where their concentrations are increasing 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Disturbance is thought to have direct impacts on ecosystems by shifting community structure and function 6 . Chloroanilines are intermediate breakdown products from the use of herbicides and pesticides in agriculture 7 , which can be found in rubber, dye, polymer and pharmaceutical industrial wastewater treatment plants 8,9 , but also in soil and natural aqueous environments 10 . These xenobiotic compounds are known to hamper both carbon and nitrogen removal in bioreactors for wastewater treatment 11 , and can represent a disturbance in sludge bioreactor systems.…”
Section: Introductionmentioning
confidence: 99%
“…The poor removal rate indicated that aromatic amines may not be adequately removed during biological wastewater treatment and hence pose a potential risk to aquatic ecology. Tasca and Fletcher (2018) reviewed that many chloroanilines persist in environment for years. 3,4-Dichloroaniline also had high persistence in sediment-water systems (Yuan et al 2017).…”
Section: Influence Of Hrt On the Removal Of Aromatic Aminesmentioning
confidence: 99%
“…Wastewater contains aromatic amines that have toxic effects on aquatic organisms, including fish, algae, and other aquatic fauna (Burkhardt-Holm et al 1999;Gosetti et al 2010;Muz et al 2017a, b;Furuhama et al 2015). 3,4-Dichloroaniline has been recognized as an endocrine disrupting chemicals (Tasca and Fletcher 2018). Therefore, the environmental risk of aromatic amines must be assessed to take appropriate management measures.…”
Section: Introductionmentioning
confidence: 99%